Development of a magnetorheological pinched mode valve for automotive semi-automotive semi-active suspension system - Ismail, Izwan (2018)
Magneto-rheological (MR) fluid is one of smart material whose rheological properties is rapidly change due to the application of the magnetic field. In this study, the new design of MR valve on pinched mode application has been proposed. The aim of this study to optimize the new MR pinched mode valve at high pressure resistance application through investigation on the effect of geometry parameter of valve mechanism. This study has been conducted through design of experiment (DOE) methodology by using 2-level factorial model. On the other hand, Finite Element Magnetic Method (FEMM) software was utilized to simulate the magnetic field generated by electromagnetic coils in MR pinched mode valve. The analysis of design concept is to verify the effective areas of pinched mode for acceptable range of pressure drop and flux density. Moreover, the investigated on pinched mode parameter can be come out by getting low viscosity with high pressure of MR fluid composition in pinched mode channel. The annular, valve gap and coil configurations are being set for various size in order to get the best magnetic field distribution and pressure drop needed. Furthermore, other material properties such as yield stress, sedimentation and material effect towards temperature and magnetic fields are also taking into consideration. The finding of this study shows, the high pressure have been applied, the high magnetic field also being produce. However, this relationship is not much significant. The pressure drop increases only 0.2 % meanwhile magnetic field shows up to 0.5 %. Optimization of geometry parameter through 2-level factorial model analysis resulting sixteen desirability value of 0.874 at maximum magnetic flux 1.06 Tesla